Empowerment of Medan Estate Village Communities in Utilizing Waste Fabric as Souvenir Products - Novida Yenni; Farihah Farihah; Pebri Hastuti; Arief Wahyudi; Debyana Debyana (Randwick International of Social Science Journal, 2022)
This Community Partnership (PKM) program generally aims to assist craft business groups, fashion business activists and PKK mothers in Medan Estate Village, Percut Sei Tuan District in managing and utilizing Fabric waste or cloth waste into souvenirs that have a selling price. In the use of Fabric waste or cloth waste, it can also reduce environmental pollution and reduce waste, especially cloth waste in Medan Estate Village, where the majority of the workers are fashion business activists and businesses related to the use of cloth. The method used in this study is the approach, training, and assistance carried out by researchers to the Medan Estate Village craft business group, fashion business activists, and PKK mothers. Partners of this PKM face various problems from lack of awareness in the need to keep the environment clean, lack of knowledge and initiative to use Fabric waste or cloth waste as souvenirs so that they have a selling value. The output and specific targets of this research are increasing public awareness in managing cloth waste into selling points. The success rate of this service activity will be measured by the results of: 1. Increasing the quality of human resources in awareness of the need to keep the environment clean from cloth waste, utilizing cloth or Fabric waste waste as souvenirs, 2. Souvenir products, 3. Logo creation, 4. Online shops and offline.